Cost and Time Comparison Analysis on Waterproof Material Aluminium Foil and Combination Cement Board and Asphalt Membrane in Roof Construction - Yopi Luthfiansyah; Achmad Alwan Damanik (NAROTAMA UNIVERSITY, Indonesia, 2021)
Existence consumer complaints regarding the quality of the building, especially related to the problem of leakage on the roof during the rainy season, made PT. Toyota Housing Indonesia improvised waterproof material in the underlayer position from conventional waterproofing (aluminum foil) to waterproofing a combination of cement board and asphalt membrane. Therefore the author will analyze the effectiveness of the two materials to overcome the problem of leakage that often occurs in roof construction.This study aims to implement the creation of